2017
DOI: 10.1098/rspb.2017.1120
|View full text |Cite
|
Sign up to set email alerts
|

Plant defences limit herbivore population growth by changing predator–prey interactions

Abstract: Plant quality and predators are important factors affecting herbivore population growth, but how they interact to regulate herbivore populations is not well understood. We manipulated jasmonate-induced plant resistance, exposure to the natural predator community and herbivore density to test how these factors jointly and independently affect herbivore population growth. On low-resistance plants, the predator community was diverse and abundant, promoting high predator consumption rates. On high-resistance plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
0
28
2
1
Order By: Relevance
“…On jasmonate-insensitive plants, for instance, aphids induce higher amounts of methyl salicylate, a SA-dependent secondary compound, compared to jasmonate-overexpressor plants (Kersch-Becker et al, 2017). Our findings differed from Kersch-Becker et al (2017), and we attributed this variation to differences in field and greenhouse experimental set-up. On wild type plants, aphid population also showed negative density-dependent growth, which might be a response to both constitutive and induced resistance expressed by these plants.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…On jasmonate-insensitive plants, for instance, aphids induce higher amounts of methyl salicylate, a SA-dependent secondary compound, compared to jasmonate-overexpressor plants (Kersch-Becker et al, 2017). Our findings differed from Kersch-Becker et al (2017), and we attributed this variation to differences in field and greenhouse experimental set-up. On wild type plants, aphid population also showed negative density-dependent growth, which might be a response to both constitutive and induced resistance expressed by these plants.…”
Section: Discussioncontrasting
confidence: 67%
“…While evidence for a trade-off between induced and constitutive resistance is still evasive, it is often suggested that the level of induced resistance expressed by plants with high levels of constitutive resistance should be lower than those expressed by plants with low levels of constitutive resistance (Karban & Baldwin, 1997). In our study, jasmonate-overexpressing plants show high JA-dependent constitutive levels of resistance (Figure 3a, McGurl et al, 1994) and were unable to activate the SA pathway ( Figure 3b, Kersch-Becker et al, 2017). We provide empirical evidence for this hypothesis by showing that high constitutive levels of resistance caused low population growth regardless of the initial density of aphids and thus did not cause negative density-dependent population growth.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations